The Influence of Attractions, Accessibility, and Facilities on The Image of The Peak Batu Roti Ciampea Tourism Object - Achyarsyah, Padri; Nugraha, Rizki Nurul; Awaloedin, Dipa Teruna (Westscience Press, 2024)
Puncak Batu Roti is a tourist attraction in Bogor Regency. The lack of diversity in tourist attractions causes fluctuations in the number of tourist visits. This title was chosen because Batu Roti Peak Ciampea is the specific location that wants to be researched, and this research tries to understand the factors that can influence the image of tourist attractions at that location. Batu Roti Peak is located on the Ciampea Limestone Mountain, Bogor. This peak is one of five peaks in the area, which also include Galau Peak, Lalana Peak, Arca Lima Peak, and Karang Gantung Peak. The location is about 17 km from the center of Bogor City. This research aims to see how tourist attractions (x) influence visiting interest (y) at the Puncak Batu Roti Tourist Attraction. Tourists who come to the Puncak Batu Roti Tourist Attraction are the objects of this research. Quantitative descriptive data analysis was used in this research. Data collected from the questionnaire was used for simple linear regression analysis. The research results show that the tourist attraction variable is in the good category with a percentage of 68.33% and the interest in visiting variable is also in the good category with a percentage of 2%. This result has a significant positive value, indicating that the more tourist attractions there are at the Puncak Batu Roti Tourist Attraction, the greater the interest in visiting. Researchers advise managers to develop new tourist attractions such as limestone educational tourism for elementary, middle and high school students by utilizing the property of local residents in the Puncak area. They also suggested building a Tourist Information Center (TIC) to provide information about all aspects of the Puncak Batu Roti Tourist Attraction for tourists.